73 Prevalence of tinnitus in Puerto Rican adults: A pilot study - Wanda Lugo Velez; Wanda Lugo-Vélez; Jorge Carrion; Annelise Hernández; Andrea Sánchez; Aida Rios; Prixemy Rodríguez (Journal of Clinical and Translational Science)
Objectives/Goals: (1) Conduct a pilot study documenting prevalence of tinnitus in a sample of Puerto Rican adults at the Audiology Clinic of the Medical Sciences Campus-University of Puerto Rico, (2) categorize patterns of tinnitus, (3) document intervention received for tinnitus, and (4) study sociodemographic characteristics of Puerto Rican adult participants with tinnitus. Methods/Study Population: A descriptive retrospective study was performed reviewing 121 clinical records of patients seen at the Audiology Intramural Clinic of the Medical Sciences Campus of the Universidad de Puerto Rico between 2022 and 2023. They were analyzed to determine the prevalence of tinnitus among this cohort. The study was submitted to the Office of Human Participants for revision and approval under the exempt category. The data were used to categorize the type of tinnitus, episodic versus constant, tonal versus non-tonal and the sociodemographic description of the sample. Results/Anticipated Results: From these 121 records, 70.2% (n = 85) were females and 29% (n = 29.8) were males. Subject ages ranged between 21 and 65 years. About 30% reported being single 30.6% (n = 37), followed by 21.5% (n = 26) reporting being married. From the 62 revised clinical records of subjects that reported tinnitus, 24% (n = 29) classified their tinnitus, in terms of how long they experience its presence, as constant, while 14% (n = 17) classified their tinnitus as intermittent. From the 62 revised clinical records, 44 participants (36.4%) described their tinnitus as tonal and 64.6 % as a complex sound of those patients 38 (31.4%) reported the tinnitus as a high-frequency pitch sound. Of the 62 patient records, the majority (98.4%) informed that they never received the treatment for tinnitus. Discussion/Significance of Impact: The results indicate that more than half of adults evaluated in the UPR Audiology Intramural Clinic (51%) had tinnitus. Age range was broad developing at any age but most prevalent in middle-aged females. Manifested permanent as a tonal or a complex sound. About 98.4% informed that they never received treatment, therefore, there is a need to ensure intervention.